2017
DOI: 10.1080/10942912.2017.1308955
|View full text |Cite
|
Sign up to set email alerts
|

Bio-chemical composition, functional, and rheological properties of fresh meat from fish, squid, and shrimp: A comparative study

Abstract: This study was conducted to evaluate bio-chemical composition, functional, and rheological properties of croaker fish (Johnius dussumieri), Indian squid (Loligo duvaucelii), and white leg shrimp (Litopenaeus vannamei) in fresh condition. The n-3 fatty acids were slightly higher in croaker fish (14.91 %) compared to that in Indian squid (13.59 %) and white leg shrimp (13.02 %). The solubility and viscosity of croaker fish proteins were significantly (p < 0.05) lower as compared to shrimp and squid proteins, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 53 publications
(67 reference statements)
2
5
3
Order By: Relevance
“…Based on the proximate analysis of the diet given to leatherback sea turtles in the present study, the dietary protein content (14% of wet weight or 85.9% of dry weight) was very high relative to dry feed pellets for other turtles and some live diets for leatherback sea turtles; such as moon jellyfish, for example, which had a reported protein content of 4.95−9.20% of dry weight (Rackmill et al, 2009). However, the protein content is similar to crude protein contents found in brine shrimp, 8.83−13.2% of wet weight (Pan et al, 1991), and squid meat, 14.2% of wet weight (Mehta & Nayak, 2017). Therefore, protein quality (amino acid profile), and a similarity to natural foodstuff compositions may be more important when designing a suitable diet for captive leatherback sea turtles.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Based on the proximate analysis of the diet given to leatherback sea turtles in the present study, the dietary protein content (14% of wet weight or 85.9% of dry weight) was very high relative to dry feed pellets for other turtles and some live diets for leatherback sea turtles; such as moon jellyfish, for example, which had a reported protein content of 4.95−9.20% of dry weight (Rackmill et al, 2009). However, the protein content is similar to crude protein contents found in brine shrimp, 8.83−13.2% of wet weight (Pan et al, 1991), and squid meat, 14.2% of wet weight (Mehta & Nayak, 2017). Therefore, protein quality (amino acid profile), and a similarity to natural foodstuff compositions may be more important when designing a suitable diet for captive leatherback sea turtles.…”
Section: Discussionsupporting
confidence: 72%
“…However, the protein content is similar to crude protein contents found in brine shrimp, 8.83−13.2% of wet weight (Pan et al, 1991), and squid meat, 14.2% of wet weight (Mehta & Nayak, 2017).…”
Section: Feed Formulation and Proposed Feed Ingredientssupporting
confidence: 69%
“…A proximate composition of white leg shrimp with 77.2% moisture, 18.8% protein, 1.3% fat, and 1.4% ash was reported (Sriket et al., 2007). Mehta & Nayak (2017) found that the Litopenaeus vannamei with a moisture content of 73.5 ± 0.3%, crude protein content of 20.0 ± 0.6%, crude fat content of 1.8 ± 0.3%, and ash content of 1.6 ± 0.2%. The results of the biochemical analysis for TVB‐N, TMA‐N, and TBA‐RS for the raw shrimp as well as processed products are presented in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, shrimp surimi products are warmly welcomed. While, compared to surimi, shrimp surimi has elastic and brittle properties due to its high cysteine protease activity, which could cause the shrimp surimi gels easily degradation and poor quality (Mehta & Nayak, 2017; Yang et al, 2020), especially for the Trachypenaeus Curvirostris . Gelling property is one of important index to evaluate the quality of shrimp surimi (Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%